A Project-Based Learning Model Using 360° Ecotourism River Videos for Teaching English Speaking Skills - Fani, Armin; Nurdian, Novi; Setyawati, Novi Suma (UIBU, 2025)
The growing demand for communicative competence in English requires pedagogical models that offer authentic, situated language practice beyond conventional classroom instruction. This Research and Development (R&D) study, employing the ADDIE model, aims to design and evaluate a Project-Based Learning (PjBL) model integrated with 360° ecotourism river videos to enhance junior high school students’ English speaking skills. The development process involved needs analysis, product design, expert validation, and a small-group trial. The final product consisted of a 360° immersive video portraying the Lok Baintan Floating Market and an accompanying PjBL-based speaking module. Validation results indicated strong pedagogical viability, with ratings from a technology expert (73.4%), an English teacher (88.6%), and students during the trial phase (92.5%). Qualitative observations further revealed heightened student engagement and motivation during speaking tasks. These findings suggest that integrating immersive video with PjBL creates an authentic, low-anxiety environment conducive to meaningful oral communication. The study contributes to ELT pedagogy by demonstrating how immersive technology can operationalize situated learning principles within project-based speaking instruction while strengthening the use of local cultural content in English language teaching.